In Vitro Study of the Action of Coconut Water and Sugar Cane Broth on Aesthetic Restorations Surfaces - Aline Lins de LIMA; Ana Maria Gondim VALENÇA; Severino Jackson Guedes de LIMA; Adílis Kalina Félix de ALEXANDRIA; Lígia Viera CLAUDINO; Naiana Braga da SILVA (Association of Support to Oral Health Research (APESB), 2007)
Objective: The present study aims to evaluate, in scanning electron microscopy, the action of the coconut water and sugar cane broth, acid beverages, on aesthetic restorations surface. Method: The sample of this study was constituted by 120 test bodies (TB), as followed: 40 TB of composite resin (CR), 40 TB of conventional glass-ionomer cement (GIC) and 40 TB resin-modified glass-ionomer cement (RM-GIC). The TBs were immersed into the beverages, and submitted to positive control (Coke) in three exposition intervals: 5, 15 and 30 minutes. After expositions, the TBs were prepared for evaluation in scanning electron microscopy, where the datas were analyzed descriptively, taking into consideration the qualitative alterations of the sample. Results: Alterations were evidenced, promoted by the sugar cane broth on the surface of CR in the interval times of 15 and 30 minutes and on the surface of conventional GIC in the three exposition periods. The coconut water just affected the surface of CR in the intervals of 15 and 30 minutes. The surface of the restorations of GIC modified by resin didn't present evaluation conditions in any of the intervals of time. Conclusion: Based in the adopted methodology and in the obtained results, it was concluded that the sugar cane broth was capable to promote superficial alteration in CR and in conventional GIC, while the coconut water just affected the CR surface.